Presence of vancomycin resistance among enterococcus isolates from stray cats in Universiti Putra Malaysia and selected neighbourhood in Sri Serdang, Selangor, Malaysia - Zulkifli, Nurul Husna; Hassan, Latiffah; Zakaria, Zunita (2010)
The present study was undertaken to determine the distribution of Enterococcus species from stray cats in Universiti Putra Malaysia and Seri Serdang and the presence of vancomycin resistance among the isolates. Fifty-five rectal swabs were collected from stray cats found in UPM and around the area of Sri Serdang. The Enterococcus species isolated were inoculated onto vancomycin resistant enterococci (VRE) agar supplemented with 8 μg/mL of vancomycin. Biochemical tests such as catalase, bile-aesculin and 6.5% NaCI were conducted to further confirm VRE isolates. Multiplex polymerase chain reaction assay (PCR) were performed for Enterococcus genus and species identification and vancomycin-resistant gene detection. Presence of Enterococcus spp. were demonstrated in every rectal sample tested. Two species were identified: Enterococcus faecalis (E. faecalis) and Enterococcus faecium (E. faecium). Among 55 isolates of Enterococcus tested, none was resistant to vancomycin at 8 μg/mL.